New species and new records of Fannia Robineau-Desvoidy (Diptera, Fanniidae) from the Brazilian Amazon Region - Wendt, Lisiane Dilli (Zootaxa, 2010)
There are 44 species of Fannia known to occur in Brazil, however, only seven of them are recorded from the Brazilian Amazon Region. Fannia bifolia sp. nov. from Parà, Brazil, is described and illustrated. Fannia itatiaiensis Albuquerque and F. pusio (Wiedemann) are newly recorded from the Brazilian Amazon Region. The known distributions of F. flavicornis Stein, F. obscurinervis (Stein), F. trimaculata (Stein) and F. trimaculatoides Couri & Pamplona are expanded. Keys to males and females of Fannia from the Brazilian Amazon Region are also provided. Copyright © 2010. Magnolia Press.
Keywords: Diptera; Fannia; Fannia Pusio; Fanniidae